A Documentary Film on Bio Gas for Farmer Groups: An Implementation of Information Media - I Wayan Khrisna Sangging Wiguna; Putu Satria Udyana Putra; Ni Putu Eka Kherismawati (Jurnal Ekspresi : Desain Komunikasi Visual dan Seni, 2023)
Simantri, also known as the Integrated Farming System, is an agricultural program designed to enhance the well-being of farmers, alleviate poverty, and reduce unemployment. One of the initiatives undertaken by Simantri is the generation of biogas. Over the past few years, the Simantri Farmer Group has engaged in the development of biogas products, resulting in the creation of a diverse range of products that cater to the needs of the local community. Nevertheless, a significant number of individuals residing in Br. Sandakan, Sulangai, Petang remain uninformed about the biogas goods. The findings of the interViews performed in Sulangai Village provided more support for this assertion, since 70% of the 30 participants expressed a lack of awareness regarding the biogas products. Approximately 30% of the participants shown awareness regarding the biogas products. The objective of this study is to disseminate knowledge to the community in Br. Sandakan by utilizing a documentary video-based methodology to introduce biogas goods. The present study employed a qualitative methodology. The research employed many methodologies, such as observation, interviews, and questionnaires. The media creation method for showcasing the biogas products of the Simantri Farmer Group in Br. Sandakan, Sulangai, Petang, involved three distinct stages: pre-production, production, and post-production. The research findings suggest that the use of documentary video-based information media is efficacious in acquainted the community in Br. Sandakan with biogas goods